Characteristics of Liquid Products from Spirulina platensis Pyrolysis under Microwave Irradiation with Activated Carbon Additive - Romaz, Mohammad Mirza Yuniar; Sukarni, Sukarni; Wulandari, Retno (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Global energy consumption has surged due to the population's rapid growth, leading to a switch to using renewable and clean energy. Among various strategies for developing renewable and clean energy, biomass pyrolysis emerged as attractive, and microwave irradiation pyrolysis is a prominent technique. This research aims to determine the ideal parameters for microwave-assisted pyrolysis of Spirulina platensis (SP) microalgae in order to produce high-value liquid products with the addition of activated carbon (AC) additives. Liquid bio-oil products were characterized concerning their calorific value, chemical bonds, and thermal stability. This research also investigates product distribution as a function of AC loading. Using 900W output power of microwave and 550 °C pyrolysis temperature, the pyrolysis process was shortened by 36.5% at 15% of AC loading. At 20% AC loading, the pyrolysis duration was shortened by 33%. This study demonstrated that the highest liquid and minimum solid residue were obtained at 20% AC loading. The heating value of liquid bio-oil with no AC additives was 35.419 MJ/kg, while at a 10% AC additive was 37.464 MJ/kg. The highest heating value was found at a 15% AC additive, which was 39.345 MJ/kg; meanwhile, at a 20% AC additive, it was 36.097 MJ/kg. These findings conclusively showed that the liquid bio-oil's quality was significantly improved by the addition of activated carbon (AC), establishing it as an attractive option for the microwave-assisted pyrolysis (MAP) process that produces advanced renewable fuels.